PENGOLAHAN AIR LIMBAH RUMAH POTONG AYAM MENGGUNAKAN BIOKOAGULAN BIJI KELOR (MORINGA OLEIFERA) SECARA BATCH - Indradini, Salsabila Azzahra Anjani; Hadisoebroto, Rositayanti; Marendra, Sheilla Megagupita Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2026)
Wastewater produced from chicken slaughterhouse (RPA) industrial activities is liquid waste containing organic compounds in high concentrations that have the potential to damage the environment if not treated first before being discharged into water bodies. This study aims to determine the effectiveness of moringa seed biocoagulant performance in removing BOD, COD, and TSS parameters. The dosage variations of moringa seed biocoagulant used in this study were 20 mg/L, 30 mg/L, 40 mg/L, 50 mg/L, 60 mg/L, and 70 mg/L with a coagulation speed of 120 rpm for 2 minutes, a flocculation speed of 20 rpm for 20 minutes, and a settling time of 2 hours. The results of the study showed that the optimum dose of moringa seed coagulant which had the lowest turbidity level was at a dose of 50 mg/L, where the optimum dose of coagulant could be effectively used in the removal of BOD, COD, and TSS pollutant parameters at a dose of 50 mg/L with a BOD removal of 49.8% from the initial characteristics of 1,683.5 mg/L to 845.12 mg/L, COD removal of 27.2% from the initial characteristics of 4,060.8 mg/L to 2,955.36 mg/L, and TSS removal of 30.4% from the initial characteristics of 427 mg/L to 297 mg/L. The RPA wastewater effluent that had been treated using moringa seed biocoagulant could remove BOD, COD, and TSS pollutant parameters in chicken slaughterhouse wastewater, but still did not meet the Quality Standards of the Minister of Environment Regulation No. 5 of 2014.